Correlation between Resilience and Mental Health with Lifestyle and Parenting Styles of Veterans\' Spouses A Case Study of Ardakan City - M. Abedini Baltork; F.S. Mir Shamsi (Afarand Scholarly Publishing Institute, 2019)
Aims: The physical and mental problems that exist among the veterans have the greatest impact on their spouses, which affects the whole family. The aim of the present study was to investigate the correlation between lifestyle and parenting style with resiliency and mental health of veteranschr('39') spouses. Instruments & Methods: This descriptive-correlational study was carried out on 170 people of veteranschr('39') spouses in Ardakan city in 2018. The subjects were selected by convenience sampling method. Data were collected by the Miller-Smith lifestyle assessment inventory, Baumrindchr('39')s parenting style inventory, Connor-Davidson resilience scale, and Goldberg and Hillier health questionnaire. Data were analyzed through SPSS 21 software using Pearson correlation coefficient method. Findings: There was a significant correlation (p=0.001) between the lifestyle with resiliency (r=0.559) and mental health (r=-0.277). Also authoritarian parenting style had a negative significant correlation (r=-0.125; p=0.042) with resilience, and positive significant correlation (r=0.094; p=0.048) with mental health. The correlation between powerful parenting style and mental health was negative and significant (r=-0.133; p=0.024). Conclusion: There is correlation between lifestyle and parenting style with resiliency and mental health of veteranschr('39') spouses.